Northern Rural and Indigenous Canadian Children’s Responses to an Open-ended Writing Task: Comparisons of Children in First and Second Year of Kindergarten - Stagg Peterson, Shelley; Friedrich, Nicola; Portier, Christine (Alberta Journal of Educational Research, 2021)
In this study, we offer a unique perspective of time spent in kindergarten and young children’s writing by presenting a multi-dimensional analysis of the writing of 72 children (5-years-old) living in northern communities in two Canadian provinces. We administered the Drawing, Writing, Talking Task (DWTT), a research-based classroom tool, in the fall and spring to children attending kindergarten in seven (six rural and one First Nations) schools. We assessed their writing in terms of their use of letters to write words, their spelling stage, and their intended content. Although the fall writing samples of children in their first year of kindergarten were significantly less developed than those of similar-aged children beginning their second year of kindergarten, by spring, the children’s writing was comparable. Our research adds to the literature on children’s learning and time spent in kindergarten by focusing on characteristics of young children’s writing, rather than test scores. Key words: writing assessment; early literacy; junior and senior kindergarten; Indigenous children’s literacy; rural children’s literacy Dans cette étude, nous offrons une perspective unique du temps passé à la maternelle et de l'écriture des jeunes enfants en présentant une analyse multidimensionnelle de l'écriture de 72 enfants âgés de 5 ans vivant dans des communautés nordiques de deux provinces canadiennes. Nous avons administré le Drawing, Writing, Talking Task (DWTT), un outil de classe basé sur la recherche, à l'automne et au printemps à des enfants fréquentant la maternelle dans sept écoles (six écoles rurales et une école des Premières nations). Nous avons évalué leur écriture en fonction de leur utilisation des lettres pour écrire des mots, de leur stade d'orthographe et du contenu visé. Bien que les échantillons d'écriture de l'automne des enfants en première année de maternelle étaient significativement moins développés que ceux d'enfants d'âge similaire commençant leur deuxième année de maternelle, au printemps, l'écriture des enfants était comparable. Notre recherche s'ajoute à la littérature sur l'apprentissage des enfants et le temps passé en maternelle en se concentrant sur les caractéristiques de l'écriture des jeunes enfants plutôt que sur les résultats des tests. Mots clés: évaluation de l'écriture; littératie précoce; maternelle et jardin d'enfants; littératie des enfants autochtones; littératie des enfants en milieu rural